SPE Oklahoma City Oil and Gas Symposium 2019
DOI: 10.2118/195191-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Using High Viscosity Friction Reducers as Fracturing Fluids for Hydraulic Fracturing Applications

Abstract: The primary purpose of using traditional friction reducers in stimulation treatments is to overcome the tubular drag while pumping at high flow rates. Hydraulic fracturing is the main technology used to produce hydrocarbon from extremely low permeability rock. Even though slickwater (water fracturing with few chemical additives) used to be one of the most common fracturing fluids, several concerns are still associated with its use, including usage of freshwater, high-cost operation, and environmental issues. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For example, a higher shear rate in excess of 3880 s −1 is observed in shale fracturing treatments [30]. In contrast, a relative low shear rate inside the fractures is ranging from 10 to 100 s −1 [31]. Thus, the influence of shear rate on rheological properties of samples with different concentrations at a constant temperature of 30 • C in a shear rate scanning from 10 −3 to 10 3 s −1 was monitored.…”
Section: Rheological Behaviors 231 Steady Rheological Behaviormentioning
confidence: 99%
“…For example, a higher shear rate in excess of 3880 s −1 is observed in shale fracturing treatments [30]. In contrast, a relative low shear rate inside the fractures is ranging from 10 to 100 s −1 [31]. Thus, the influence of shear rate on rheological properties of samples with different concentrations at a constant temperature of 30 • C in a shear rate scanning from 10 −3 to 10 3 s −1 was monitored.…”
Section: Rheological Behaviors 231 Steady Rheological Behaviormentioning
confidence: 99%
“…The findings reveal that varying the number of -OH group and oxygen atoms, as well as chain length and branching of carrier fluids, has a substantial impact on intermolecular interactions and that rheological features of a hydraulic fracturing fluid may be controlled [19,20]. High viscosity friction reducers (HVFRs), which are typically high molecular weight polyacrylamides, have been recommended as a biopolymer alternative [21]. In over 26 case studies, the fluid demonstrated greater proppant transport capabilities, nearly 100 percent maintained conductivity, cost savings, a 50 percent decrease in chemical usage, less operational equipment on site, a 30 percent reduction in water consumption, and less environmental concerns.…”
Section: Galactomannan As a Key Ingredient In Biopolymersmentioning
confidence: 99%
“…The slick water fracturing fluid is composed of drag-reducing agents combined with bactericide, clay stabilizer, cleanup additives, and other auxiliary agents to form a complete formulation system, which has a good drag-reducing effect. 6,7 The drag resistance of the fluid restricts the flow of the fluid in the pipeline, resulting in low pipeline throughput and increased energy consumption. The polymer dragreducing method is to inject a small amount of high-molecular hydrocarbon polymers into the fluid and reduce the drag resistance in the turbulent state.…”
Section: Introductionmentioning
confidence: 99%
“…The successful application of the fracturing fluid in shales in the 1990s gradually formed the concept of hydraulic fracturing. , After years of field operation and laboratory experiments, it is generally considered that the slick water fracturing fluid is more suitable for the exploitation of unconventional oil and gas deposit resources and it is easy to form large-scale complex cracks. The slick water fracturing fluid is composed of drag-reducing agents combined with bactericide, clay stabilizer, cleanup additives, and other auxiliary agents to form a complete formulation system, which has a good drag-reducing effect. , The drag resistance of the fluid restricts the flow of the fluid in the pipeline, resulting in low pipeline throughput and increased energy consumption. The polymer drag-reducing method is to inject a small amount of high-molecular hydrocarbon polymers into the fluid and reduce the drag resistance in the turbulent state.…”
Section: Introductionmentioning
confidence: 99%